Implementation of an Advanced Practice Provider–Led Scholarly Project Review Committee - Pandey, Shila; Preti, Kelly; Cazeau, Naomi; Fearon, Nkechi; McGrath Ehinger, Leigh; Jacob, Helen; Tipian, Caroll; Goldberg, Jessica I.; Zakak, Nicole; Haviland, Kelly (Journal for nurse practitioners, 2025)
The engagement of advanced practice providers (APPs) in evidence-based practice (EBP), quality improvement (QI), and research activities enhances job satisfaction and contributions to high-quality health care. However, APPs encounter barriers that limit participation in, and leadership of, such activities. An APP-led QI, EBP, and Research Review Committee was established to support the development, implementation, and dissemination of scholarly projects. Among 67 project proposals, 40 (60%) were completed, 19 (28%) are ongoing, and 8 (12%) were abandoned or postponed. An APP-led peer review process is a feasible and effective approach to overcoming barriers faced by APPs to engage in QI, EBP, and research. •The development of an advanced practice provider–led committee creates a structure for facilitating and monitoring evidence-based practice, quality improvement, and research projects.•When advanced practice providers are given support to develop and implement scholarly projects, the number and quality of nurse practitioner–led projects increase.•A formalized structure for engagement in scholarly projects allows for data collection and informs the need for additional professional development support for advanced practice providers.